Significant usage of slab and wall form technique in industrialised building systems (IBS) for low cost highrise apartments construction - Abdul Rahman, Redzuan (2006)
The Industrialised Building Systems (IBS) concept adopted and applied during early sixties in Malaysia. The key reason in adopting this system essentially for housing construction is to enhance the development of low cost housing project for the lower income group. Using IBS will address issues such as quality, materials wastage, delays, dirty and hazardous worksites. In the structural classification of IBS, steel formworks are listed one of the traditional or common types of IBS. This master project conducted to study the basic concept, application and the significant usage of slab and wall form technique for low cost high-rise apartment construction industry. The study further assessed the benefit of using slab and wall form technique in high-rise low cost apartment construction. The methodology adopted for the study includes literature review, observation, interviews and using questionnaire survey. These questionnaires distributed to the respondents, which represent the professional in construction industry that have experience and knowledge on the slab and wall form technique technology and the construction procedure. The study evaluated the on ongoing and the completed project using this systems and established that this technique has the ability to reduce the time and labour involved in the project. Elemental cost analysis and cost simulation toward different types of formwork used to establish the justification of the significant usage of the tunnel form system as selected slab and wall form technique. The study concluded that the slab and wall form technique feasible alternative construction method that can improve construction industry with respect to the accomplishing better quality of works and increasing productivity. The study also determined that the adoption of this slab and wall form technique in the construction of the low cost high-rise apartments greatly benefit the building industry in various aspects such as reducing the construction cost, better planning and design coordination, speed of construction, minimising manpower on site, better quality construction, environmentally friendly, and improved site safety